Beyond Conventional Therapies: Molecular Dynamics of Alzheimer's Treatment through CLOCK/BMAL1 Interactions - Haskologlu, Ismail C.; Erdag, Emine; Sehirli, Ahmet Ozer; Uludag, Orhan; Abacioglu, Nurettin (Current Alzheimer Research, 2023)
Background: Alzheimer's Disease (AD) represents a neurodegenerative disorder characterized by cognitive and behavioral impairments significantly hindering social and occupational functioning. Melatonin, a hormone pivotal in regulating the body's intrinsic circadian rhythm, also acts as a catalyst in the breakdown of beta-amyloid deposits, offering a promising therapeutic approach for AD. The upregulation of Brain and Muscle ARNT-Like 1 (Bmal1) gene expression, stimulated by melatonin, emerges as a potential contributor to AD intervention. Current pharmacological interventions, such as FDA-approved cholinesterase inhibitors and the recently authorized monoclonal antibody, Lecanemab, are utilized in AD management. However, the connection between these medications and Bmal1 remains insufficiently explored. Objective: This study aims to investigate the molecular effects of FDA-endorsed drugs on the CLOCK: Bmal1 dimer. Furthermore, considering the interactions between melatonin and Bmal1, this research explores the potential synergistic efficacy of combining these pharmaceutical agents with melatonin for AD treatment. Methods: Using molecular docking and MM/PBSA methodologies, this research determines the binding affinities of drugs within the Bmal1 binding site, constructing interaction profiles. Results: The findings reveal that, among FDA-approved drugs, galanthamine and donepezil demonstrate notably similar binding energy values to melatonin, interacting within the Bmal1 binding site through analogous amino acid residues and functional groups. Conclusion: A novel therapeutic approach emerges, suggesting the combination of melatonin with Lecanemab as a monoclonal antibody therapy. Importantly, prior research has not explored the effects of FDA-approved drugs on Bmal1 expression or their potential for synergistic effects.
Keywords: chronotherapy